2003
DOI: 10.1111/j.1432-2277.2003.tb00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acute selective endothelin-receptor-A blockade on renal hemodynamics in a rat model of chronic allograft rejection

Abstract: We have recently demonstrated up-regulation of renal endothelin (ET) synthesis in a rat model of chronic renal allograft rejection. Treatment with a selective ET-A receptor antagonist improved survival and reduced functional and morphological kidney damage. However, the underlying mechanisms have not yet been elucidated, as ET exhibits both hemodynamic and inflammatory properties. Therefore, in the present study we investigated acute hemodynamic effects of the selective ET-A receptor antagonist LU 302146 (LU) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These findings are compatible with a direct immunomodulatory role for ET A receptors during allograft rejection [190,196]. Braun et al [197] reported that ET A receptor blockade with LU135252 prevented long-term deleterious changes on renal allograft function and morphology independently from systemic blood pressure and did not lower proteinuria, strongly arguing against any effect on glomerular hemodynamics and upregulation of renal ET-1 synthesis in a rat model of renal allograft rejection in which a role for the ET A receptor has been demonstrated [198].…”
Section: Transplantationmentioning
confidence: 74%
“…These findings are compatible with a direct immunomodulatory role for ET A receptors during allograft rejection [190,196]. Braun et al [197] reported that ET A receptor blockade with LU135252 prevented long-term deleterious changes on renal allograft function and morphology independently from systemic blood pressure and did not lower proteinuria, strongly arguing against any effect on glomerular hemodynamics and upregulation of renal ET-1 synthesis in a rat model of renal allograft rejection in which a role for the ET A receptor has been demonstrated [198].…”
Section: Transplantationmentioning
confidence: 74%
“…Acute ET A -receptor blockade did not induce important haemodynamic effects in kidneys undergoing chronic rejection. The lack of response to ET A -receptor blockade suggested that the beneficial effect of ET receptor antagonists in this model was likely to be due to improvement of renal morphology [85]. Long-term studies using systemic doses of ET antagonists are required to clarify these issues.…”
Section: Dual Angiotensin II Receptor Type 1 and Endothelin A Receptomentioning
confidence: 93%